A new Proteocephalidean tapeworm, Gangesia (Gangesia) bendsurensis n.sp. from fresh water cat fish, Wallago attu at Beed district (M.S.), India - Jaywant Dhole1, Sunil Anand1, *Yogesh Reddy1, Hemlata Wankhede2, (International Multidisciplinary Research Journal, 2011)
The present communication deals with the Proteocephalidean tapeworm Gangesia (Gangesia) bendsurensis n.sp. from Wallago attu at Bendsura dam, Beed district. The worms comes closer to all the known species of this genus scolex globular, rostellar hooks 35 – 47 in number, mature segment broader than long, testes 170 – 190 in number, ovary butterfly shaped, vitellaria follicular.